[PP.13.15] LATE AORTIC ANEURYSM AND STENT FRACTURE SECONDARY TO SEVERE ARTERIAL HYPERTENSION IN CORRECTED COARCTATION AND CHRONIC RENAL FAILURE. (September 2017) - Gasser, S.; Meier, R.; Koestenberger, M.; Sorantin, E.; Gamillscheg, A.; Oberwalder, P.; Knez, I.; Nagl, B.
Abstract : Objective: Aortic stent rupture with concomitant aortic aneurism resulting from arterial hypertension has not been described as yet. A patient, now aged 24 years, with coarctation has been operated at the age of three weeks with an end to end anastomosis of the aorta. Besause of a residual stenosis the toddler has been re-operated a day later. The procedure has been further complicated by renal failure with subsequent temporary hemodyalisis. Design and method: During the following years, arterial blood pressure has remained within the normal range, showing a gradient of 10 mmHg. From 2006 onwards, the patient has developed arterial hypertension, which has been difficult to cope with despite multiple antihypertensive medication. During this time, renal function has been constantly reduced with creatinine around 2, 1 mg/dl and a reduced glomerular filtration rate. In 2006, MR-Angiography of the aortic arch showed a hypoplastic segment of several centimeters. This observation led to an implantation of a CP-stent in order provide more stability to the hypoplastic aortic segment. Six months later, MR-angiography and chest x-ray revealed a correctly positioned, intact stent. Results: Until 2012 MR-angiographies have been avoided because of the progressive renal dysfunction, which culminated in evaluation for renal transplantation (creatinine 6, 2 mg/dl). Native MR-angiography revealed an aortic aneurysm within the stented segment and chest x-ray showed in the same region several stent fractures. Subsequently, the aortic segment with the stent has been surgically removed and replaced by a prothetic inter-ponate. Postoperatively, the patient had been subjected to hemodialysis for a week and renal transplantation has been postponed. Conclusions: In summary, it is likely that the development of both renal failure and the aortic aneurysm has been enhanced and aggravated by the severe, drug restistant hypertension. It remains to discussion whether or not stent fracture has been also been facilitated by severe hypertension.